Incidence, Risk Factors, and Outcomes of Severe Hypoxemia After Cardiac Surgery - Wang, Dashuai; Ding, Xiangchao; Su, Yunshu; Yang, Peiwen; Du, Xinling; Sun, Manda; Huang, Xiaofan; Yue, Zhang; Sun, Fuqiang; Xie, Fei; Liu, Chao (Frontiers in Cardiovascular Medicine, 2022)
Background: Hypoxemia is common in patients undergoing cardiac surgery, however, few studies about severe hypoxemia (SH) after cardiac surgery exist. The objectives of this study were to clarify the incidence, risk factors and outcomes of SH after cardiac surgery. Methods: Patients undergoing cardiac surgery from 2016 to 2019 in a single center were enrolled and were divided into two groups based on whether postoperative SH developed. Independent risk factors for SH were identified by univariate and multivariate analysis. Model selection statistics were applied to help determine the most parsimonious final model. Results: SH developed in 222 of the 5,323 included patients (4.2%), associated with poorer clinical outcomes. Six independent risk factors for SH after cardiac surgery were identified by multivariate analysis, including surgical types, white blood cell count, body mass index, serum albumin, cardiopulmonary bypass time, and intraoperative transfusion of red blood cells. After comprehensively considering the discrimination, calibration and simplicity, the most appropriate and parsimonious model were finally established using four predictors, including white blood cell count, body mass index, cardiopulmonary bypass time, and intraoperative transfusion of red blood cells. A nomogram and a web-based risk calculator based on the final model were constructed to facilitate clinical practice. Patients were stratified into three risk groups based on the nomogram and clinical practice. Conclusions: SH was common after cardiac surgery, associated with poorer clinical outcomes. A parsimonious final model with good discrimination, calibration and clinical utility was constructed, which may be helpful for personalized risk assessment and targeted intervention.